2019
DOI: 10.3389/fpls.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous or End-of-Day Far-Red Light on Tomato Plant Growth, Morphology, Light Absorption, and Fruit Production

Abstract: Shading by sunlit leaves causes a low red (R) to far-red (FR) ratio that results in a low phytochrome stationary state (PSS). A low PSS induces an array of shade avoidance responses that influence plant architecture and development. It has often been suggested that this architectural response is advantageous for plant growth due to its positive effect on light interception. In contrast to sunlight, artificial light sources such as LEDs often lack FR, resulting in a PSS value higher than solar light (∼0.70). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
226
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(257 citation statements)
references
References 48 publications
25
226
3
3
Order By: Relevance
“…This difference between short-term and long-term responses indicates that the efficiency of light utilization for photosynthesis may have acclimated to far-red radiation during long-term growth. Possible changes include modifications in leaf thickness, chlorophyll content (Table 1), chl a:b ratio (Gommers et al, 2013;Kalaitzoglou et al, 2019), PSI:PSII ratio, electron transport and photosynthetic capacity, rubisco content and activity (Chow et al, 1990a;Chow et al, 1990b;Anderson et al, 1995), as well as in the biosynthesis of photoprotective pigments carotenoids and anthocyanins (Li and Kubota, 2009;Stutte et al, 2009;Kalaitzoglou et al, 2019).…”
Section: Canopy Quantum Yield: Short-term Versus Long-term Response Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference between short-term and long-term responses indicates that the efficiency of light utilization for photosynthesis may have acclimated to far-red radiation during long-term growth. Possible changes include modifications in leaf thickness, chlorophyll content (Table 1), chl a:b ratio (Gommers et al, 2013;Kalaitzoglou et al, 2019), PSI:PSII ratio, electron transport and photosynthetic capacity, rubisco content and activity (Chow et al, 1990a;Chow et al, 1990b;Anderson et al, 1995), as well as in the biosynthesis of photoprotective pigments carotenoids and anthocyanins (Li and Kubota, 2009;Stutte et al, 2009;Kalaitzoglou et al, 2019).…”
Section: Canopy Quantum Yield: Short-term Versus Long-term Response Tmentioning
confidence: 99%
“…Perhaps the most powerful effect is the simulation of shade through FR supplementation, often without reducing light intensity in the PAR region. This change has been reported to promote leaf expansion in various leafy greens, fruiting vegetables, and ornamental species, which increases growth primarily through increased radiation capture (Casal et al, 1987;Goins et al, 2001;Li and Kubota, 2009;Stutte et al, 2009;Park and Runkle, 2017;Kalaitzoglou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As for the light quality, low R-to-FR ratios increased the accumulation of biomass into the stems at the expense of leaves. However, fruit production was improved under these light conditions possibly due to a positive impact on flowering acceleration (Kalaitzoglou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from plant morphological alterations, changes in the R : FR ratio also lead to the redistribution of growth and dry matter within the plants, as indicated by an increased shoot/root ratio and soluble sugar levels under radiation with a low R : FR ratio. Kalaitzoglou et al (2019) reported that additional FR light applied as continuous and EOD treatment increased total dry mass of tomato plants in the vegetative growth stage, as well as the fruit number per plant, fresh fruit weight per plant and average fruit fresh mass. Similarly, higher total plant dry mass and higher fruit yield in tomato grown under additional FR radiation were reported by Zhang et al (2019b).…”
Section: Fr and Yield Qualitymentioning
confidence: 98%